Towards design pattern definition language. (30th September 2011) - Khwaja, Salman; Alshayeb, Mohammad; Fayad, Mohamed E.; Singh, Shivanshu K.
SUMMARY Design patterns are rapidly gaining acceptance in the software community not only as reusable constructs for software development but also for the documentation of the software architectural design. Most of the existing design pattern languages describe design patterns using a combination of a natural language, UML‐style diagrams and complex mathematical or logic based formalisms, which makes them hard for programmers to understand. In this paper we propose a design pattern definition language (DPDL) based on XML which can be used for sharing design patterns' implementation details among developers. DPDL is easy to understand and use. It provides unambiguous description of the patterns and is extensible. DPDL also has the flexibility of defining design patterns in a generic term to be used as templates. Copyright © 2011 John Wiley & Sons, Ltd.